Engineering a norcoclaurine synthase for one-step synthesis of (S)-1-aryl-tetrahydroisoquinolines - Zhang, Man; Huang, Zheng-Yu; Su, Ying; Chen, Fei-Fei; Chen, Qi; Xu, Jian-He; Zheng, Gao-Wei (Bioresources and bioprocessing, 2023)
Tetrahydroisoquinoline alkaloids (THIQAs) are ubiquitous compounds with important pharmaceutical and biological activity. Their key N -heterocyclic structural motifs are synthesised via Pictet–Spengler (P–S) reaction by norcoclaurine synthases (NCS) in plants. The synthesis of 1-aryl-tetrahydroisoquinoline alkaloids has attracted increasing attention due to their antitumor and antivirus activities. Herein, the L68T/M97V mutant of NCS from Thalictrum flavum with improved activity was developed by semi-rational design. This mutant not only showed higher catalytic performance (> 96% conversion) toward benzaldehyde and dopamine over the wild-type enzyme, but also catalysed the P–S reaction of the bulky substrate 4-biphenylaldehyde and dopamine with high conversion (> 99%) for the effective synthesis of 1-aryl-THIQA. In terms of stereoselectivity, all products synthesised by the L68T/M97V mutant showed high optical purity (92–99% enantiomeric excess). Graphical Abstract